Innovative approaches to the organization process of the school courses teacher qualifications - Кочерга, Олександр (Educological discourse, 2013)
The article is devoted to the problems connected with introducing of creditmodule system training courses organization for pedagogical specialists of In-Service Teacher Training Institute of Kyiv Boris Grinchenko University.